Pandangan Hadis Terhadap Fenomena Meminta Gift di Media Sosial Tiktok - Muhammad Dimas Yasyifa; John Supriyanto; Sulaiman Muhammad Nur (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
In the modern era like today, many things happen because of the influence of increasingly developing technology, especially social media that makes it easier for people to communicate with various platforms. Actually, the presence of social media should have a good influence, but many people misuse it, so that the phenomenon of begging on the TikTok social media platform appears which is not in accordance with Islamic teachings and the prohibition in the hadith on begging narrated by Imam Ahmad, Imam Muslim, Imam Al-Bukhari. This study aims to determine the views of the hadith on the prohibition of begging on TikTok social media using a qualitative research method of library research. The results of this research study are that the views of the hadith on the prohibition of begging have important relevance in the context of the Phenomenon of asking for gifts on Tiktok social media that begging online is haram because it is deceitful and takes advantage of the situation to get as many gifts as possible. The conclusion is that for those who are still energetic and strong, it is forbidden to beg. With this view, the behavior of asking for gifts on Tiktok can be responded to wisely according to Islamic teachings and social media ethics.